“Tourist App”- to find a locations (International Journal of Engineering and Computer Science, 2017)
This paper describes the planning and development of location. Mobile commercial enterprise application is employed to seek out commercial enterprise place. This application is employed in each robot platform. owing to this app folks will notice actual location. The frontend of this app is robot. Backend is Xamp server, php server. This app helps for any someone for locating and visiting any location at intervals less time. Through this app we will visit the place in future and there's no want of guide. This app can advocate the places wherever we will visit the place. Emergency is additionally provided during this app. once a user thinks that he's in peril he will contact others